2003
DOI: 10.1164/rccm.200306-737oc
|View full text |Cite
|
Sign up to set email alerts
|

Rhinovirus-induced Interferon-γ and Airway Responsiveness in Asthma

Abstract: The majority of asthma exacerbations are caused by respiratory infections, with rhinovirus (RV) being the most common virus. Recent evidence has suggested that decreased generation of IFN-gamma is associated with more severe colds and delayed elimination of virus. Whether the generation of IFN-gamma also has any relationship to general features of asthma severity has yet to be determined. To evaluate this hypothesis, peripheral blood mononuclear cells from 19 subjects with atopy and asthma were incubated with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
62
1
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 99 publications
(69 citation statements)
references
References 28 publications
5
62
1
1
Order By: Relevance
“…Perhaps individuals with asthma have increased protease activation leading to increased susceptibility to infection. Alternatively, several studies have provided evidence that asthma is associated with impaired innate antiviral responses (20,21). In our study, peripheral blood mononuclear cell innate responses to HRV or RSV between children with and without asthma were similar, suggesting that increased H1N1 infectivity in individuals with asthma is not the result of a defect in innate immunity.…”
Section: Discussionsupporting
confidence: 61%
“…Perhaps individuals with asthma have increased protease activation leading to increased susceptibility to infection. Alternatively, several studies have provided evidence that asthma is associated with impaired innate antiviral responses (20,21). In our study, peripheral blood mononuclear cell innate responses to HRV or RSV between children with and without asthma were similar, suggesting that increased H1N1 infectivity in individuals with asthma is not the result of a defect in innate immunity.…”
Section: Discussionsupporting
confidence: 61%
“…In our studies, neither atopy nor asthma were associated with impaired virus‐induced interferon responses (IFN‐γ or IFN‐α responses to RSV, RV, or TLR3), which differs from results of several previously published studies 7, 8, 28. The reason for the lack of association could be related to either age or cell source.…”
Section: Discussioncontrasting
confidence: 99%
“…Similarly, studies of mononuclear cells and cloned T cells from peripheral blood of atopic asthmatic adults and children have described a Th2 bias to antigen 7, 10. In addition, there is evidence that deficient interferon responses in asthma may promote virus‐induced wheezing illnesses, and in children, the development of asthma 8, 13, 14, 15, 16, 17. Further investigation of the immune response to microbial and antigenic stimuli in allergic and asthmatic adults are needed, particularly in the urban population, where asthma prevalence and morbidity is especially high.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the skewing of the cytokine phenotype away from an IFN-g-induced intracellular pathogen-clearing response toward a cytokine-directing ''reparative response'' may leave the host at risk for an exacerbated viral infection. Previous reports have demonstrated that decreased IFN-g production is associated with more severe rhinovirus infection and a delay in the elimination of the virus (23). This reduced type 1 response to rhinovirus has been reported to increase both asthma severity and viral shedding during rhinovirus infection.…”
Section: Cytokine Polarization and The Exacerbation Of Pulmonary Viramentioning
confidence: 95%